PENGARUH CARBON RISK MANAGEMENT, BOARD DIVERSITY, SUSTAINABILITY COMMITTEE DAN ENVIRONMENTAL PERFORMANCE TERHADAP CARBON EMISSION DISCLOSURE - Maharani Prasti Amira, (2021)
The study was conducted to determine the effect of carbon risk management, board diversity, sustainability committee, and environmental performance on carbon emission disclosure. This study is a quantitative study conducted on 23 non-financial companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. Data obtained using STATA v.16 with the results of the hypothesis test state that environmental performance has a significant positive effect on carbon emissions disclosures. Meanwhile, carbon risk management, board diversity, and sustainability committee have no effect on carbon emission disclosure.